Review on space weather in Latin America. 1. The beginning from space science research - Denardini, Clezio Marcos (2016)
The present work is the first of a three-part review on space weather in Latin America. It comprises the evolution of several Latin American institutions investing in space science since the 1960s, focusing on the solar–terrestrial interactions, which today is commonly called space weather. Despite recognizing advances in space research in all of Latin America, this review is restricted to the development observed in three countries in particular (Argentina, Brazil and Mexico), due to the fact that these countries have recently developed operational centers for monitoring space weather. The review starts with a brief summary of the first groups to start working with space science in Latin America. This first part of the review closes with the current status and the research interests of these groups, which are described in relation to the most significant works and challenges of the next decade in order to aid in the solving of space weather open issues.